Trypanotolerant livestock, a sustainable and essential component of livestock production systems under trypanosomosis risk in East and Central Africa - D'Ieteren, G.D.M. (European Union, 2001)
Trypanotolerance, the ability of some livestock species and breeds to survive, reproduce and remain productive under trypanosomosis risk without the aid of trypanocidal drugs, was recognised and exploited by farmers long before research on trypanotolerance began. The exploitation of trypanotolerant breeds is practiced as a major option for sustainable livestock production in 19 countries in the most humid parts of West and Central Africa. There are now N'Dama herds in nearly all West and Central African countries which could be the source of genetic material for further dissemination. Experimental and field studies reviewed in this chapter are providing the basic tools with which the trypanotolerance trait can be identified and exploited.